2018
DOI: 10.1589/rika.33.591
|View full text |Cite
|
Sign up to set email alerts
|

Criterion-related Validity and Reliability of Surae Muscle Tendon Unit Stiffness Measured Using a Custom Made Passive Torque Indicator

Abstract: Purpose] To confirm the criterion-related validity and reliability of surae muscle tendon unit stiffness measured using a custom-made passive torque indicator (CPTI), a portable device composed of an angle-adjustable foot plate and strain gauge. The data were compared to readings obtained using an isokinetic dynamometer. [Subjects and Methods] Fourteen healthy young adults participated in this study. Torques at four angles of dorsiflexion of the ankle joint of the subjects were recorded using the CPTI and a dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Before and after the stretching in both the NAC and AAC conditions, the maximum ROM of ankle dorsiflexion and the passive plantarflexion torque of the affected limb were measured using the custom-made passive torque indicator (Takei Scientific Instruments Co. Ltd., Japan). The criterion-related validity of the stiffness measured with this equipment compared with that with isokinetic dynamometer (BIODEX ver.3) has been previously reported 14 ) . The custom-made passive torque indicator consisted of an angle-adjustable foot plate with strain gauge, digital angle gauge, and metal base frame, which allowed measurements of static plantarflexion torque and ankle dorsiflexion angle when the foot plate is moved to the passive dorsiflexion direction.…”
Section: Participants and Methodsmentioning
confidence: 72%
See 1 more Smart Citation
“…Before and after the stretching in both the NAC and AAC conditions, the maximum ROM of ankle dorsiflexion and the passive plantarflexion torque of the affected limb were measured using the custom-made passive torque indicator (Takei Scientific Instruments Co. Ltd., Japan). The criterion-related validity of the stiffness measured with this equipment compared with that with isokinetic dynamometer (BIODEX ver.3) has been previously reported 14 ) . The custom-made passive torque indicator consisted of an angle-adjustable foot plate with strain gauge, digital angle gauge, and metal base frame, which allowed measurements of static plantarflexion torque and ankle dorsiflexion angle when the foot plate is moved to the passive dorsiflexion direction.…”
Section: Participants and Methodsmentioning
confidence: 72%
“…In this study, the calf muscle stiffness based on a custom-made passive torque indicator displayed a high inter-day reproducibility. Our previous work on healthy young adults 14 ) indicated that a fixed error between stiffness obtained from custom-made passive torque indicator and that from dynamometer exists. However, the validity of the stiffness between the two approaches is of no concern as this study is interested in the stiffness after the stretching intervention.…”
Section: Discussionmentioning
confidence: 99%